Sound environment quality in nursing units in Chinese nursing homes: A pilot study. Issue 4 (December 2020) - Xie, Hui; Zhong, Bingzhi; Liu, Chang
Recent studies have investigated sound environment in nursing homes. However, there has been little research on the sound environment of nursing units. This research sought to address this gap. Subjective evaluations were gathered using questionnaire surveys of 75 elderly residents and 30 nursing staff members in five nursing units of five nursing homes in Chongqing, China. Background noise level and reverberation time were measured in five empty bedrooms, five occupied bedrooms and five occupied nursing station areas, in five nursing units. The subjective evaluation results indicate that the residents stay in the nursing units for most of their waking hours. The residents and nursing staff had strong preferences for natural sounds, with the lowest perceptions of these in the nursing units. The background noise level in all the occupied bedrooms exceeded Chinese standards for waking and sleeping hours. Only 20% of the occupied nursing station areas were below the allowable noise level for recreation and fitness room during sleeping hours. The nursing station area was identified as the main source of noise in the unit during waking hours. The average background noise level of the occupied bedrooms was 3–12 dBA higher than that of the empty bedrooms during sleeping hours. Attention should be given to the implementation of noise specifications for sleeping hours. The reverberation time of the bedrooms was within the range of 0.44–0.68 s, and in the nursing station areas it was 0.63–1.54 s.